Decomposing the effect of social policies on population health and inequalities: An empirical example of unemployment benefits. Issue 7 (November 2014) - Ferrarini, Tommy; Nelson, Kenneth; Sjöberg, Ola
Aim : The purpose of this study is to discuss and empirically contrast different conceptualizations and operationalizations of social policies in analysing health and educational differences in health cross-nationally. Methods : Country-level institutional and expenditure data on unemployment benefit schemes and individual-level data from the EU-SILC for 23 countries were used to analyse the association between unemployment benefits and self-assessed health for individuals with different educational attainment. Results : The analyses indicate that higher coverage rate (i.e. the proportion of the relevant population eligible for benefits) is associated with better self-related health among both low- and high-educated individuals, but is not linked to smaller educational differences in health. In contrast, replacement rate (i.e. the amount of benefits received) in isolation is not related to self-assessed health. However, in countries where coverage rates are high, higher replacement rates are associated with better health among both low- and high-educated individuals and smaller educational differences in health. Conclusions : Decomposing unemployment benefit programmes into two main dimensions – the proportion in the labour force covered by such programmes and the replacement rate received in case of unemployment – may present further insights into institutional mechanisms linking macro-level social policies to individual-level health outcomes.